The Effect of the Application of Differentiated Learning as an Effort to Increase Student Learning Motivation in Biology Subjects - Krisnawati, Weny Astri (PPSDP International Journal of Education, 2024)
The purpose of this study was to increase students’ interest in the biology curriculum. Three components of differentiated learning, namely visual, auditory, and kinesthetic, were used in this study. This research was a two-cycle classroom action research project that began with a pre-cycle. Each cycle consists of planning, action, observation, assessment, and reflection. For the 2022-2023 academic year, the research focused on class XII, even semester students at SMAN 1 Belitang III OKU Timur. Based on the results of research involving 29 students, the number of students who completed pre-cycle activities was 8 (27 points, 58 percent), while students who did not complete were 21 (72 points, 42 percent), with an average score of 55 points, 17. In cycle I, there was an increase in the number of students who completed 15 (51 points, 72 percent), while the number of students who did not complete was 14 (48 points, 28 percent), with an average score of. This study proves that the use of differentiated learning can increase the motivation to learn biology in class XII, even for semester students of SMAN 1 Belitang III OKU Timur in the 2022-2023 academic year. There was a very high increase in cycle II compared to the previous cycle, with the number of students who reached the minimum brilliance criteria as many as 28 students (96,55%), while the number of students who did not complete was 1 person.